2021
DOI: 10.1111/ijcp.14158
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of rituximab in patients with neuromyelitis optica spectrum disorder: A real‐world study from Turkey

Abstract: Background: Neuromyelitis optica spectrum disorders (NMOSD) are a group of antibody-mediated chronic inflammatory diseases of the central nervous system.Rituximab is a monoclonal antibody that leads to a reduction in disease activity.Objective: To evaluate the efficacy of rituximab as monotherapy in NMOSD and to determine whether the efficacy varies depending on the presence of antibodies in this cohort.Method: This multicentre national retrospective study included patients with NMOSD treated with rituximab at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The EDSS scores decreased from 3.94 ± 1.98 to 2.67 ± 1.54, and ARR decreased from 1.45 ± 1.53 to 0.15 ± 0.34. No radiological activity was observed or assessed at intervals of one year, which is similar to our study [19]. Both the RIN-1 study and the meta-analysis conducted by Gao et al showcased promising results of RTX in this patient group [20,21].…”
Section: Nmosdsupporting
confidence: 89%
“…The EDSS scores decreased from 3.94 ± 1.98 to 2.67 ± 1.54, and ARR decreased from 1.45 ± 1.53 to 0.15 ± 0.34. No radiological activity was observed or assessed at intervals of one year, which is similar to our study [19]. Both the RIN-1 study and the meta-analysis conducted by Gao et al showcased promising results of RTX in this patient group [20,21].…”
Section: Nmosdsupporting
confidence: 89%
“…Effects on ARR. A total of 26 studies [2,3,5,7,8,[10][11][12]17,[19][20][21][23][24][25][26][27][28][32][33][34][35][36][37][38][39] were reported ARR before and after RTX therapy in patients with NMOSD. The results of Meta-analysis showed that the ARR of NMOSD patients after RTX treatment was significantly decreased by 1.45, and the difference was statistically significant (WMD = 1.45, 95% CI: 1.24-1.66, P < .01).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
“… 17 , 18 The effectiveness of BCD in SN-NMOSD is currently uncertain. 13 Consequently, the second objective of our study was to investigate whether BCD treatment leads to distinct alterations in serum proteomes for each NMOSD subtype.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Limited information is available regarding BCD in SN-NMOSD; however, anti-CD20 may reduce relapse rates in these patients. 13 , 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation